The metric and color profiling of eggs produced by F2 Mahkota Arab chickens - Narzassi, Angga Bintang; Daryono, Budi Setiadi (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Genetic quality improvement in local chickens can be achieved through crossbreeding, which has enhanced productivity and egg quality, satisfying consumer demand. To improve the quality of livestock products, it is crucial to assess the egg quality of chickens. This study evaluated the quality of eggs produced by F2 Mahkota Arab chickens bred from crossbreeding with F1 Mahkota Arab chickens. The research comprised several stages: chicken rearing, tests for egg shape index calculation, yolk index, albumin index, Haugh unit, and eggshell colour observation. The obtained results were compared with those of F1 Mahkota Arab chicken, Arab chicken, and Layer chicken. According to the study's findings, the F2 Mahkota Arab had an egg with a standard egg shape of 70% as per the egg shape index. The F2 Mahkota Arab chicken had a mean yolk index of 0.37±0.00, a mean albumin index of 0.121±0.005, and a mean Haugh unit of 91.99±1.13. The shell colour of their eggs belongs to the orange-white group, and the egg quality, including egg shape index, albumin index and Haugh unit, is higher than other chicken groups. Furthermore, the shell colour of F2 Mahkota Arab chicken eggs is whiter than other chicken groups.